A Woman’s Expression for Freedom in Sabrina Carpenter’s “Feather”: A Radical Feminist Reading - Pebrawaninggil, Ganeshiwi Intan; Nurhayati, Sulasih (Journal of English Language and Education, 2025)
The depiction of female liberation in mainstream media has emerged as a critical focus within feminist discourse. This article examines how Sabrina Carpenter's music video "Feather" represents women's defiance against patriarchal oppression through radical feminist theory and Roland Barthes' semiotic analysis. The study employs a qualitative descriptive method to analyze particular visual scenes and symbols, including religious imagery (church altars, coffins, and crosses), outfit selections (black bridal dress, pink sporty outfit), gestures, facial expressions, and narrative irony (e.g., scenes of male catcallers being hit by a truck), in order explain themes of female autonomy. The signs are examined through the lenses of denotation, connotation, and myth. The findings indicate that “Feather” converts patriarchal religious and cultural symbols into instruments of emancipation and critiques societal conventions related to gender, authority, and female visibility in public spaces. This research highlights that pop media, when critically analyzed, can function as a platform for feminist resistance and ideological transformation.